Analysis of an open nucleus breeding programme for Djallonke sheep in the Ivory Coast. 2. Response to selection on body weights - Yapi-Gnoare, C.V.; Rege, J.E.O.; Oya, A.; Alemayehu, N. (Cambridge University Press, 1997)
A selection programme was set up in 1983 in the Ivory Coast to improve the growth and live weight of the indigenous Djallonke sheep using an open nucleus breeding system. Selection was based on male individual weights at 80, 180 and 365 days of age. Multiple sires were used in farmers' flocks. Individual animal model, using average numerator relationship was used to estimate breeding values from which genetic trends were derived. This paper reports results of the analyses of 10 417 records of 80-days weights (WT80) and 365- (WT365) day weights, respectively, of lambs from the nucleus. Phenotypic trends exhibited substantial annual fluctuation during the study period. The heaviest weights were obtained in 1986 (10.1 kg) for WT80, 1984 (23.3 kg) for WT180 and 1985 (33.7 kg) for WT365. There was an annual decline of 152g (P<0.05) in WT80 mainly (-180 g/year) due to negative environmental trend. The phenotypic and environmental trends for WT180 were -703 and -721 g/year, respectively, while the corresponding values for WT365 were -931 and -956 g/year. Overall mean weights of the ram lambs at the three ages were 9.9, 23.3 and 33.7 kg., respectively in the base year and 9.3, 17.8 and 28.2 kg, respectively in the final year. Breeding values increased by 28, 11 and 14 g/year for WT80, WT180 and WT365, respectively. Results of this study indicate that genetic progress can be made in growth performance of Djallonke sheep if reasonable levels of animal management as well as selection pressure are maintained.